Professional supervision practice under new public management : a study of the perspectives of probation officers and service managers in the community probation service : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Social Policy and Social Work, Massey University, Palmerston North, New Zealand - O'Donoghue, Kieran Barry (Massey University, 1999)
This thesis examines professional supervision practice under new public management from the perspectives of probation officers and service managers in the Community Probation Service. In particular, the research explores the participants’ philosophy of professional supervision, their recent supervision experiences, and their aspirations and expectations with regard to professional supervision. In order to provide a background for an informed analysis and discussion of the research findings, the thesis discusses the key themes in the social service supervision and new public management literature. It also examines the Community Probation Service’s context and the history of new public management and professional supervision in this organisation. The thesis is a qualitative study that is informed by social work practice theory and utilises the phenomenological and hermeneutic approaches. The research findings show that amongst the participants there was: (a) an unclear philosophy of supervision; (b) minimal recent experience of supervision and little ownership or support for the agency supervision project; (c) a belief that the context increased their need for supervision, but at the same time reduced their ability to receive or participate in it; (d) an expectation that professional supervision would assist them to work more effectively with clients and staff; (e) an expectation of good committed supervisors who would support and help them develop; and (f) an expectation that the agency would support professional supervision through resourcing, guidelines, accredited supervisors and the establishment of a learning culture. The major implications of these findings are that: (1) there is a need for staff to be socialised into professional social service supervision; (2) that the professional supervision programme within the Community Probation Service, as currently implemented, is unlikely to be successful; and (3) that professional social service supervision needs to be focused upon persons and their environments, rather than upon the agency.
Keywords: Probation officers; Professional supervision; Social service supervision; Fields of Research::390000 Law, Justice and Law Enforcement::390400 Law Enforcement::390405 Correctional theory and services; penology